A histological study of atherosclerotic characteristics in age-related macular degeneration. Issue 3 (March 2022) - Wang, Jingchao; Zhang, Hongpeng; Ji, Jing; Wang, Lixuan; Lv, Wenxin; He, Yuan; Li, Xuan; Feng, Guangyu; Chen, Kinon
Abstract: This study investigated the pathogenesis of age-related macular degeneration (AMD) using histological methods that are commonly used for atherosclerotic vascular disease (ASVD). 1 normal, 3 early dry AMD, and 1 late dry AMD eyes were obtained from the Lions Eye Bank of Oregon and systematically dissected. They were stained with hematoxylin and eosin, Oil red O, Masson, Elastica van Gieson, Alizarin red, and Prussian blue. Additionally, the normal and late dry AMD eyes were immunostained for a-smooth muscle actin, CD45, and CD68 with Nile red and DAPI. Correlations were found between severity of AMD and lipid accumulation in the deep sclera (+), numbers of drusen between the Bruch's membrane and retinal pigment epithelium (RPE) (+), amount of collagen in the deep sclera (+), and amount of elastin in the deep sclera (-) (P < 0.1). Geographic atrophy, RPE detachment, and abnormal capillary shape and distribution in the choriocapillaris were observed in the fovea of late AMD. There were no stenosis, plaque, hemorrhage, and calcification. Additionally, late AMD tended to have higher smooth muscle thicknesses of the choroidal vascular walls, lower numbers of T lymphocytes in the choroid, and higher numbers of macrophages near the RPE and in the choroid relative to normal (P < 0.1). Macrophages-derived foam cells were detected near the Bruch's membrane in late AMD. Therefore, the present study showed many histological characteristics of ASVD in AMD, which suggests an association between them; however, there were also some histological characteristics of ASVD that were not found in AMD, which indicates that there exist pathogenic differences between them. The results generally support the vascular model of AMD, but some details still need clarification. Abstract : Histology; Staining; Atherosclerotic vascular disease; Atherosclerosis; Blood vessel.